FAIR Photos – Transforming a Collection of Two Million Historical Press Photos into Five Star Data - Leon van Wissen; Nico Vriend; Antoinet Nijssen; Lars Vereecken; Menno den Engelse (Journal of Open Humanities Data)
The FAIR Photos project enriched the metadata of the Press Agency De Boer collection, comprising two million press photos (1945–2005) from the North Holland Archives in The Netherlands. By linking photographs to external datasets such as Wikidata, and creating thesauri in the Simple Knowledge Organization System (SKOS) – interlinked with external thesauri such as the Art & Architecture Thesaurus (AAT) – the project significantly improved the collection’s accessibility for research and cultural heritage purposes. The enriched metadata, published in CSV and RDF formats, are available as open data in the DANS Data Station Social Sciences and Humanities (https://doi.org/10.17026/SS/7VD3ME). Funded by CLARIAH, the project promoted the FAIR principles (Findability, Accessibility, Interoperability, and Reusability) and Linked Open Data (LOD) adoption within the archive.